1966
DOI: 10.1161/01.res.19.4.774
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Release and Left Ventricular Pressure in the Isolated Heart

Abstract: In an isolated dog heart, perfused with blood from an anesthetized donor, left ventricular performance was observed during periods in which the left ventricle either contracted isovolumically or was allowed to eject saline. Heart rate and left ventricular end-diastolic pressure were comparable in both. Ventricular performance, as judged by peak systolic ventricular pressure, declined relatively rapidly during isovolumic loading when initial systolic pressures were higher. The efflux of norepinephrine (NE) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1968
1968
2001
2001

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Later work by Sarnoff et al lent additional support to the second hypothesis (4). A subsequent publication from our laboratory gave evidence implicating the third (5). Recently, Sonnenblick et al called attention to the increase in ventricular compliance observed to accompany an abrupt increase in the pressure developed by the ventricle (6).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Later work by Sarnoff et al lent additional support to the second hypothesis (4). A subsequent publication from our laboratory gave evidence implicating the third (5). Recently, Sonnenblick et al called attention to the increase in ventricular compliance observed to accompany an abrupt increase in the pressure developed by the ventricle (6).…”
mentioning
confidence: 70%
“…To accomplish this isolated lungs, in lieu of a donor dog, were used to oxygenate the blood perfusing the heart. In addition, the blood was dialyzed on its return from the heart by passing it through a dialysis unit (Travenol U210) as reported in a previous study (5). Catecholamine determinations were likewise made as previously described, using a modification of the trihydroxyindole method (5).…”
Section: Methodsmentioning
confidence: 99%
“…We also perfused the cephalic region of the animals, including the aortic and carotid baroreceptors, at constant pressure to reduce the likelihood of alterations in the levels of circulating catecholamines. A further possibility, suggested from previous studies in isolated dog hearts, is that shortening of action potential following increases in LVPP may have been secondary to release of noradrenaline from endogenous stores at sympathetic nerve endings (Monroe, LaFarge, Gamble, Hammond & Morgan, 1966). This effect has also been demonstrated in vivo (LaFarge, Monroe, Rosenthal & Hammond, 1970).…”
Section: Discussionmentioning
confidence: 93%
“…We attribute the great reduction in ectopic frequency in denervated myocardium to myocardial catecholamine depletion rather than loss of sympathetic and parasympathetic afferent or efferent neuronal pathways because pressure load induced arrhythmias occur after acute denervation 12 Acute pressure loading of myocardium induces release of proarrhythmic noradrenaline from the myocardium, presumably from sympathetic neurones 5…”
mentioning
confidence: 96%